Đào tạo giáo viên sử dụng và sản xuất tài nguyên giáo dục mở bằng phương pháp đào tạo trực tuyến - Đậu, Mạnh Hoàn (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Today, online training has become a popular and highly effective training method in education. Open Educational Resource is a new teaching technology supporting teachers in online teaching. In education activity, the effectiveness of teaching depends on the teachers as they play a very important role in training and education. The teachers bring positive impacts to teaching activities at schools as well as to high educational efficiency. Therefore, universities and educational institutions need to build strategies to train users and develop open educational resources to improve the efficiency and quality of education.      In this article, the author identifies issues in training teachers to use and produce open educational resources by online training which is considered to be the fastest approach for teachers to acquire technology as well as overcome the issue of lacking training specialists in Vietnam at present.